A low post-thickening branched soda swelling thickener and a preparation method thereof

CN117510743BActive Publication Date: 2026-10-09SICHUAN DOWELL SCI & TECH INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311363928.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2026-10-09
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

[0003]但是相比缔合型丙烯酸酯增稠剂,目前市场上对非缔合纯碱溶胀型丙烯酸酯增稠剂研究的较少,现有技术主要是采用常规的丙烯酸乙酯、丙烯酸、甲基丙烯酸等为原料,通过乳液聚合的方式进行共聚,制得具有常规亲水与疏水结构的聚合物,其在应用后与涂料等体系的其它组份发生分子内与分子间相互作用,达到为涂料等增稠的目的

Benefits of technology

[0026] 1. The low-thickening branched soda ash swelling thickener of the present invention has scientifically and rationally selected raw materials, specifically:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117510743B_ABST
    Figure CN117510743B_ABST
Patent Text Reader

Abstract

The application belongs to the field of water-based additives, and particularly relates to a low post-thickening branched soda swelling thickener and a preparation method thereof. The low post-thickening branched soda swelling thickener is prepared from the following raw materials in percentage by weight: 7-10% of a monobasic acid ester monomer, 0.5-5% of a dicarboxylic acid ester monomer, 10-20% of a short-chain acrylic acid ester monomer, 1-5% of a long-chain acrylic acid ester monomer, 0.05-1% of a multi-functionality unsaturated vinyl cross-linking monomer, 0.1-10% of a thiol monomer, 0.5-5% of a reactive stable monomer, 1-3% of a reactive emulsifier, 0.05-0.5% of an initiator, and the balance of deionized water. The low post-thickening branched soda swelling thickener has the characteristics of high post-thickening efficiency, low post-thickening amplitude and good thermal storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water-based additives, specifically relating to a low-post-thickening branched soda ash swelling thickener and its preparation method. Background Technology

[0002] Currently, water-based coatings and adhesives are increasingly used in various fields. However, they commonly suffer from high post-thickening viscosity, which increases exponentially with storage time, causing inconvenience. Thickeners, as key additives in water-based coatings and adhesives, play a crucial role in their storage performance, rheological properties, and processing performance, and have a decisive impact on their post-thickening viscosity. Acrylic thickeners are among the most widely used thickeners in water-based coatings and adhesives due to their high thickening efficiency, adjustable application performance, and low cost.

[0003] However, compared to associative acrylate thickeners, there is currently less research on non-associative alkali-swellable acrylate thickeners on the market. Existing technologies mainly use conventional ethyl acrylate, acrylic acid, methacrylic acid, etc., as raw materials, and copolymerize them through emulsion polymerization to obtain polymers with conventional hydrophilic and hydrophobic structures. After application, these polymers interact with other components in coatings and other systems through intramolecular and intermolecular interactions to achieve the purpose of thickening. However, existing technologies cannot effectively control the molecular structure, nor can they introduce special hydrophilic and hydrophobic groups, especially the composition and distribution of hydrophilic and hydrophobic segments, and molecular weight distribution. The performance of the prepared products is unstable, and the raw materials and technologies used cannot simultaneously meet the requirements of high thickening efficiency and low post-thickening. After application in coatings and other systems, there is a common problem of high post-thickening, which restricts the further application of acrylate thickeners.

[0004] Therefore, based on this, the technical solution of the present invention is proposed. Summary of the Invention

[0005] To address the problems existing in the prior art, the present invention provides a low-post-thickening branched soda ash swelling thickener, prepared from the following raw materials in weight percentages: 7-10% monocarboxylated acrylate monomer, 0.5-5% dicarboxylated acrylate monomer, 10-20% short-chain acrylic acid ester monomer, 1-5% long-chain acrylic acid ester monomer, 0.05-1% polyfunctional unsaturated vinyl crosslinking monomer, 0.1-10% mercapto monomer, 0.5-5% reactive stabilizing monomer, 1-3% reactive emulsifier, 0.05-0.5% initiator, and the balance being deionized water.

[0006] Preferably, the monocarboxylated acrylate monomer is one or a combination of two of methacrylic acid and acrylic acid;

[0007] And / or, the dicarboxyacrylate monomer is one or a combination of maleic acid and itaconic acid.

[0008] Preferably, the short-chain acrylate monomer is one or a combination of two or more of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, isobutyl acrylate, n-butyl methacrylate, and isobutyl methacrylate.

[0009] And / or, the long-chain acrylate monomer is one or a combination of two or more of isooctyl acrylate, isooctyl methacrylate, dodecyl acrylate, dodecyl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, octadecyl acrylate, and octadecyl methacrylate.

[0010] Preferably, the multifunctional unsaturated vinyl crosslinking monomer is an acrylate monomer containing three or more unsaturated vinyl groups, and the multifunctional unsaturated vinyl crosslinking monomer is one or a combination of two or more of pentaerythritol triacrylate, trimethylolpropane triacrylate, ethoxytrihydroxypropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.

[0011] And / or, the mercapto-containing monomer is one or a combination of two or more of mercaptoethanol, butyl mercaptopropionate, and mercaptopropionic acid;

[0012] And / or, the reactive stable monomer is one or a combination of two or more of sodium vinyl sulfonate, sodium 2-methylallyl sulfonate, and sodium allyloxyhydroxy sulfonate;

[0013] And / or, the initiator is one of ammonium persulfate, sodium persulfate, and potassium persulfate.

[0014] Preferably, the reactive emulsifier is a reactive emulsifier containing a vinyl structure, and the structural formula of the reactive emulsifier is shown in Formula I.

[0015]

[0016] Wherein, R is an alkyl group, the number of carbon atoms in the alkyl group is an integer between 7 and 20, X is H or SO3NH4, and n is an integer between 10 and 40.

[0017] Based on the same technical concept, another aspect of the present invention is to provide a method for preparing a low-post-thickening branched soda ash swelling thickener, the preparation method comprising the following steps:

[0018] (1) Add a portion of reactive emulsifier, monomers containing monocarboxylated acrylates, monomers containing dicarboxylated acrylates, short-chain acrylate monomers, long-chain acrylate monomers, multifunctional unsaturated vinyl crosslinking monomers, mercapto-containing monomers, and reactive stable monomers to deionized water in sequence, and stir until the system is stable to obtain monomer pre-emulsion.

[0019] (2) Mix the initiator with deionized water to obtain an initiator solution;

[0020] (3) Mix the remaining reactive emulsifier and deionized water, then add part of the monomer pre-emulsion and part of the initiator solution, and carry out seed polymerization;

[0021] (4) After the seed polymerization is completed, the remaining monomer pre-emulsion and the remaining initiator solution are added dropwise simultaneously to maintain the reaction temperature until the emulsion polymerization reaction is completed, and a low-thickening branched soda ash swelling thickener is obtained.

[0022] Preferably, in step (3), the temperature for seed polymerization is 82–86°C;

[0023] And / or, in step (4), the dripping time is 90 to 150 minutes.

[0024] Preferably, in step (4), the weight-average molecular weight of the low-thickening branched soda ash swelling thickener obtained is 1000-4000 g / mol, and the molecular weight distribution is 1.4-2.0.

[0025] The beneficial effects of this invention are as follows:

[0026] 1. The low-thickening branched soda ash swelling thickener of the present invention has scientifically and rationally selected raw materials, specifically:

[0027] The reactive emulsifier and reactive stabilizing monomer can overcome the drawback of the ineffective adsorption of hydrophilic and hydrophobic groups of the thickener by the emulsifier in traditional acrylic thickeners, improve the adsorption rate of the thickener and other components in the system, thereby improving the thickening efficiency. At the same time, the introduction of reactive emulsifier and stabilizing monomer can reduce the addition of acidic hydrophilic monomers, thereby increasing the stability of emulsion polymerization.

[0028] The initiator decomposes at a certain temperature to generate active free radicals. These free radicals initiate polymerization reactions of various vinyl monomers and appropriate amounts of multifunctional crosslinking monomers. During the reaction, the molecular weight and distribution are controlled by a sufficient amount of mercapto-containing monomers, allowing the degree of crosslinking to be controlled within a certain range. This results in a thickener product with a branched structure. In water-based coatings or adhesives, the carboxyl groups are neutralized by alkali to generate carboxylate ions. Under electrostatic repulsion, the original emulsion particles hydrolyze into a water-soluble polymer with a branched structure. Due to its low molecular weight, the subsequent thickening effect is greatly reduced. At the same time, the branched structure can improve its adsorption efficiency with other components in the system, thus improving the thickening efficiency. The prepared thickener emulsion has the characteristics of simultaneously achieving both thickening efficiency and post-thickening. Moreover, the system is less affected by ions after application, and the system viscosity stability is good. In particular, it solves the problem of high post-thickening that cannot be solved by existing technologies.

[0029] 2. The preparation method of the low-thickening branched soda ash swelling thickener of the present invention is easy to control and conducive to large-scale production. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0031] Figure 1 This is a storage stability diagram of test sample-1 in Table 1 after being placed at 25℃ for 30 days.

[0032] Figure 2 Table 1 shows the storage stability of Dow ASE-60 after 30 days at 25°C.

[0033] Figure 3 This is a storage stability diagram of test sample-1 in Table 1 after being placed at 4℃ for 30 days.

[0034] Figure 4 Table 1 shows the storage stability of Dow ASE-60 after 30 days at 4°C.

[0035] Figure 5 This is a storage stability diagram of test sample-1 in Table 1 after being placed at 50℃ for 30 days.

[0036] Figure 6 Table 1 shows the storage stability of Dow ASE-60 after 30 days at 50°C.

[0037] Figure 7 This is a storage stability diagram of test sample-2 in Table 2 after being placed at 25℃ for 30 days.

[0038] Figure 8 Table 2 shows the storage stability of Dow ASE-60 after 30 days at 25°C.

[0039] Figure 9 This is a storage stability diagram of test sample-2 in Table 2 after being placed at 4℃ for 30 days.

[0040] Figure 10 Table 2 shows the storage stability of Dow ASE-60 after 30 days at 4°C.

[0041] Figure 11 This is a storage stability diagram of test sample-2 in Table 2 after being placed at 50℃ for 30 days.

[0042] Figure 12 Table 2 shows the storage stability of Dow ASE-60 after 30 days at 50°C. Detailed Implementation

[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0044] Example 1

[0045] This embodiment provides a method for preparing a low-post-thickening branched soda ash swelling thickener, the preparation method comprising the following steps:

[0046] (1) Add 25g of deionized water to the emulsification tank, and slowly add 3.2g of reactive emulsifier SR-20 (20%) (Japanese Aidico product), 10g of acrylic acid, 20g of methacrylic acid, 15g of itaconic acid, 38.98g of ethyl acrylate, 10g of isooctyl acrylate, 0.02g of pentaerythritol tetraacrylate, 1.0g of mercaptoethanol, and 4.0g of sodium vinyl sulfonate while stirring at 200rpm. Stir for 30min until the system is stable to obtain a monomer pre-emulsion.

[0047] (2) Dissolve 0.15g of potassium persulfate in 20g of deionized water to obtain an initiator solution for dropwise addition; dissolve 0.15g of potassium persulfate in 2g of deionized water to obtain a seed emulsion initiator solution;

[0048] (3) Add 100g of deionized water and 3.2g of reactive emulsifier SR-20 (20%) (Japanese Aidico product) to the reactor. After stirring, heat to 82℃, then add 4wt.% of monomer pre-emulsion and seed emulsion initiator solution. After the emulsion system turns blue, add the remaining monomer pre-emulsion and initiator solution dropwise. The dropwise addition is completed in 90min. After keeping warm for 60min, cool down and filter to obtain the low-thickness branched soda ash swelling thickener. The weight average molecular weight is 2560g / mol and the molecular weight distribution is 1.58, as determined by GPC.

[0049] To verify the effect, the low-thickening branched soda ash swelling thickener (test sample-1) obtained in this embodiment was subjected to thickening application tests. The thickening efficiency, thixotropy, storage stability at 50℃, storage stability at 4℃, and storage stability at 25℃ of the thickener emulsion were tested respectively.

[0050] The application process is as follows: Acrylic resin RA1260 and polyurethane resin RU2301 from Sichuan Dawei Technology Co., Ltd. are compounded at a mass ratio of 2:1. Then, the pH of the mixed resin is adjusted to 8.0-9.0 with ammonia water. Test sample-1 (diluted with deionized water 1:1) is slowly added while stirring at about 200 rpm. The final viscosity of the mixed resin emulsion is adjusted to about 4000 cps (3# 6 rpm). Then, other properties of the thickened emulsion are tested. The performance of test sample-1 and the application data of a competitor's product on the market are shown in Table 1.

[0051] Table 1

[0052]

[0053]

[0054] As can be seen from Table 1 above, under the condition of comparable thixotropy, the thickening efficiency of test sample-1 is higher than that of competing products on the market. At the same time, the storage stability of the emulsion at 25℃ and 50℃ after application is better than that of competing products, and the thickening range after emulsion viscosity is significantly smaller than that of competing products.

[0055] Example 2

[0056] This embodiment provides a method for preparing a low-post-thickening branched soda ash swelling thickener, the preparation method comprising the following steps:

[0057] (1) Add 25g of deionized water to the emulsification tank, and slowly add 3.2g of reactive emulsifier SR-20 (20%) (Japanese Aidico product), 5g of acrylic acid, 30g of methacrylic acid, 5g of itaconic acid, 48.98g of ethyl acrylate, 10g of n-butyl acrylate, 0.02g of dipentaerythritol pentaacrylate, 2.0g of butyl mercaptopropionate and 3.0g of sodium allyl hydroxysulfonate while stirring at 200rpm. Stir for 30min until the system is stable to obtain monomer pre-emulsion.

[0058] (2) Dissolve 0.12g of sodium persulfate in 20g of deionized water to obtain an initiator solution for dropwise addition; dissolve 0.08g of sodium persulfate in 2g of deionized water to obtain a seed emulsion initiator solution;

[0059] (3) Add 100g of deionized water and 3.2g of reactive emulsifier SR-20 (20%) (Japanese Aidico product) to the reactor. After stirring, heat to 86℃, then add 6wt.% of monomer pre-emulsion and seed emulsion initiator solution. After the emulsion system turns blue, add the remaining monomer pre-emulsion and initiator solution dropwise. The dropwise addition is completed in 150min. After keeping warm for 60min, cool down and filter to obtain the low-thickness branched soda ash swelling thickener. The weight average molecular weight is 3240g / mol and the molecular weight distribution is 1.49, as determined by GPC.

[0060] To verify the effect, the low-thickening branched soda ash swelling thickener (test sample-2) obtained in this embodiment was subjected to thickening application tests. The thickening efficiency, thixotropy, storage stability at 50℃, storage stability at 4℃, and storage stability at 25℃ of the thickener emulsion were tested respectively.

[0061] The application process is as follows: Acrylic resin RA1260 and polyurethane resin RU2301 from Sichuan Dawei Technology Co., Ltd. are compounded at a mass ratio of 2:1. Then, the pH of the mixed resin is adjusted to 8.0-9.0 with ammonia water. Test sample-2 (diluted with deionized water at a ratio of 1:1) is slowly added while stirring at about 200 rpm. The final viscosity of the mixed resin emulsion is adjusted to about 4000 cps (3#6 rpm). Then, other properties of the thickened emulsion are tested. The performance of test sample-2 and the application data of a competitor's product on the market are shown in Table 2.

[0062] Table 2

[0063]

[0064]

[0065] As can be seen from Table 2 above, under the condition of comparable thixotropy, the thickening efficiency of test sample-2 is higher than that of competing products on the market. At the same time, the storage stability of the emulsion at 25℃ and 50℃ after application is better than that of competing products, and the thickening range of the emulsion after viscosity is significantly smaller than that of competing products.

[0066] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A low-post-thickening branched soda ash swelling thickener, characterized in that, It is prepared from the following raw materials in weight percentage: 7-10% monocarboxylated acrylate monomers, 0.5-5% dicarboxylated acrylate monomers, 10-20% short-chain acrylate monomers, 1-5% long-chain acrylate monomers, 0.05-1% polyfunctional unsaturated vinyl crosslinking monomers, 0.1-10% mercapto monomers, 0.5-5% reactive stabilizing monomers, 1-3% reactive emulsifiers, 0.05-0.5% initiators, and the balance being deionized water; The reactive stable monomer is one or a combination of two of sodium vinyl sulfonate and sodium 2-methylallyl sulfonate. The structural formula of the reactive emulsifier is shown in Formula I. Formula I Wherein, R is an alkyl group, and the number of carbon atoms in the alkyl group is an integer between 7 and 20; X is H or SO3NH4, and n is an integer between 10 and 40.

2. The low-thickening branched soda ash swelling thickener according to claim 1, characterized in that, The monocarboxylated acrylate monomer is one or a combination of two of methacrylic acid and acrylic acid; And / or, the dicarboxyacrylate monomer is one or a combination of maleic acid and itaconic acid.

3. The low-thickening branched soda ash swelling thickener according to claim 1, characterized in that, The short-chain acrylate monomer is one or a combination of two or more of the following: methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, isobutyl acrylate, n-butyl methacrylate, and isobutyl methacrylate. And / or, the long-chain acrylate monomer is one or a combination of two or more of isooctyl acrylate, isooctyl methacrylate, dodecyl acrylate, dodecyl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, octadecyl acrylate, and octadecyl methacrylate.

4. The low-thickening branched soda ash swelling thickener according to claim 1, characterized in that, The multifunctional unsaturated vinyl crosslinking monomer is one or a combination of two or more of pentaerythritol triacrylate, trimethylolpropane triacrylate, ethoxytrihydroxypropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate. And / or, the mercapto-containing monomer is one or a combination of two or more of mercaptoethanol, butyl mercaptopropionate, and mercaptopropionic acid; And / or, the initiator is one of ammonium persulfate, sodium persulfate, and potassium persulfate.

5. The preparation method of the low-thickening branched soda ash swelling thickener according to any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: (1) Add a portion of reactive emulsifier, monomers containing monocarboxylic acrylate, monomers containing dicarboxylic acrylate, short-chain acrylate monomers, long-chain acrylate monomers, polyfunctional unsaturated vinyl crosslinking monomers, mercapto-containing monomers, and reactive stable monomers to deionized water in sequence, and stir until the system is stable to obtain monomer pre-emulsion. (2) Mix the initiator with deionized water to obtain an initiator solution; (3) Mix the remaining reactive emulsifier and deionized water, then add part of the monomer pre-emulsion and part of the initiator solution, and carry out seed polymerization; (4) After the seed polymerization is completed, the remaining monomer pre-emulsion and the remaining initiator solution are added dropwise simultaneously to maintain the reaction temperature until the emulsion polymerization reaction is completed, and a low-thickening branched soda ash swelling thickener is obtained.

6. The preparation method of the low-post-thickening branched soda ash swelling thickener according to claim 5, characterized in that, In step (3), the temperature for seed polymerization is 82~86℃; And / or, in step (4), the dripping time is 90~150 min.

7. The preparation method of the low-thickening branched soda ash swelling thickener according to claim 5, characterized in that, In step (4), the weight-average molecular weight of the low-thickening branched soda ash swelling thickener obtained is 1000~4000 g / mol, and the molecular weight distribution is 1.4~2.0.

Citation Information

Patent Citations

  • Highly-crosslinked acrylate copolymer as well as preparation method and application thereof as thickening agent

    CN109957062A

  • Low-shear alkali-swelling acrylate associative thickener and preparation method thereof

    CN114989370A